2012
DOI: 10.1021/es300712g
|View full text |Cite
|
Sign up to set email alerts
|

Blood Concentrations of Persistent Organic Pollutants and Prediabetes and Diabetes in the General Population of Catalonia

Abstract: The aim was to analyze the effects of body mass index (BMI), low-dose exposure, mixtures of persistent organic pollutants (POPs), and lipid adjustment on the relationship between POP concentrations and diabetes and prediabetes in the general adult population of Catalonia (Spain). Serum concentrations of POPs were measured by gas chromatography with electron-capture detection in 886 participants in a health interview survey. The highest concentrations of all POPs analyzed were found in subjects who had diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 37 publications
3
49
2
Order By: Relevance
“…According to Lee et al (2007), the dioxin-like PCBs showed strong positive associations with diabetes. Also HCB was found to be associated with diabetes in several studies (Wu et al, 2013;Gasull et al, 2012;Codru et al, 2007;Glynn et al, 2000). Whereas we found a strong positive association between PCB118 and "Diabetes", we did not find such an association between marker PCBs and "Diabetes".…”
Section: Diabetescontrasting
confidence: 96%
“…According to Lee et al (2007), the dioxin-like PCBs showed strong positive associations with diabetes. Also HCB was found to be associated with diabetes in several studies (Wu et al, 2013;Gasull et al, 2012;Codru et al, 2007;Glynn et al, 2000). Whereas we found a strong positive association between PCB118 and "Diabetes", we did not find such an association between marker PCBs and "Diabetes".…”
Section: Diabetescontrasting
confidence: 96%
“…Cross-sectional studies performed in other races or ethnicities also showed significant associations between OC pesticides and type 2 diabetes, but their results were not as strongly graded as ours (Codru et al 2007;Cox et al 2007;Philibert et al 2009;Turyk et al 2009). Other previous cross-sectional, longitudinal studies and a meta-analysis, with different adjustment levels, reported that serum levels of OCPs and/or PCBs were positively associated with diabetes risk (Airaksinen et al 2011;Gasull et al 2012;Lee et al 2011;Wu et al 2013). They found a significantly higher concentration of DDTs (especially DDE) in patients with diabetes than without the disease.…”
Section: Discussionmentioning
confidence: 93%
“…High OR in RignellHydbom et al study compared to certain studies except fish consumers (Turyk et al, 2009;Philibert et al, 2009) (Gasull et al, 2012).…”
Section: Comparison Studiesmentioning
confidence: 89%